Clinical features, pathogens, and mortality of endogenous endophthalmitis: A 10-year retrospective review in Northern Taiwan - Yu-Hsun Chuang; Po-Jung Lai; Tzyy-Chang Ho; Chung-May Yang; Chang-Hao Yang; Chang-Ping Lin; Yi-Ting Hsieh; Tso-Ting Lai; Ta-Ching Chen; Po-Ting Yeh (Taiwan Journal of Ophthalmology, 2025)
PURPOSE: To comprehensively review the epidemiology, clinical features, causative pathogens, primary infection sites, and mortality of endogenous endophthalmitis (EE). MATERIALS AND METHODS: A retrospective review was conducted on patients diagnosed with EE at National Taiwan University Hospital between 2014 and 2024. Clinical data, including patient demographics, underlying systemic diseases, identified pathogens, infection sources, and outcomes, were analyzed. RESULTS: Ninety-nine eyes from 91 patients with EE were enrolled. The majority of cases were bacterial (61.5%), followed by fungal infections (27.5%). A small number of cases had no documented pathogens. Bilateral involvement was more frequent in fungal cases. Among patients with endogenous bacterial endophthalmitis (EBE), Klebsiella pneumoniae was the most common causative pathogen, typically originating from liver abscesses. Diabetes mellitus (DM) was the most frequently associated systemic disease. In endogenous fungal endophthalmitis (EFE), Candida albicans was the predominant pathogen. Patients with EFE had a higher prevalence of bilateral involvement and increased mortality. Overall, the visual prognosis for EE patients was poor, regardless of the causative pathogen. Generalized estimating equations analysis identified female sex (P = 0.014), EFE (P < 0.001), bilateral involvement (P < 0.001), and DM (P = 0.014) as risk factors for mortality in EE. CONCLUSION: EE remains a vision-threatening condition. K. pneumoniae, frequently associated with liver abscesses, is the leading cause of EBE. C. albicans is the most common pathogen in EFE. However, patients with bilateral EFE have a higher mortality rate. Overall, final visual outcomes were generally poor, with many patients experiencing severe vision impairment despite treatment.